Examining the neoliberalization of space in Indonesia through the lens of Ahmadin's "sociology of space" - Misbawati, Mrs. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
Ahmadin's book "Sociology of Space: Concepts, Theories, and Case Studies" responds to academic concerns about the frequent understanding of space as merely a passive physical entity. This book envisions space as a dynamic social product, imbued with power relations, and a battleground for meaning. Through a comprehensive study approach, Ahmadin takes readers on an exploration of how spaces—from cities and villages to malls and sidewalks to parks—are produced, consumed, and reproduced through social relations. The book is structured in a well-organized manner, beginning with a conceptual mapping and the roots of sociological thought in space, exploring key theories from leading thinkers such as Henri Lefebvre, David Harvey, and Michel Foucault, and concluding with a depiction of reality in various case studies of several cities in Indonesia.